Comparison of different tests for the diagnosis of Salmonella typhi in Nineveh Governorate - Bushra Shlla (College of Education for Pure Sciences, 2021)
Salmonella typhi is one of the most common causes of typhoid fever in Iraq. The aim of this study was to test the synergistic between different tests for the diagnosis of S. typhi . It was found, there are ability for preparing local Media which can be used instead of Blood agar for diagnosing typhoid fever by using dates, alfalfa and fish extractors. Both fish and dates extractors were used to prepare a local medium as well as alfalfa and fish. The results showed that dates - fish medium are more efficient  than blood agar and alfalfa - fish medium to isolate S. typhi. When contrasting culture results with Widal test data of laboratories , it had shown differences in these results because only (57)% from Widal test was confirmed by culture. When Widal test results were evaluated which is done in different health analysing laboratories in Nineveh Governorate by using Widal test (dilution method) the results showed great differences of results whether result type (positive or negative) or kind of antigens which showed  positive results. Leukocyte count was done as a test to enhance the diagnosis of this microbe, it was clear that there is a relation between typhoid fever and decreasing white blood cell count.